Analysis and optimization of chemical-technological systems for methanol synthesis with the aid of computer modeling - Осипенко, Ульяна Юрьевна (Eastern-European Journal of Enterprise Technologies, 2012)
In this article we show results by the development of a computer model for the methanol synthesis process, allowing to find optimal values for process parameters, monitor the decrease in catalyst activity and carry out computational studies